2020
DOI: 10.1002/app.49205
|View full text |Cite
|
Sign up to set email alerts
|

Development of biodegradable natural rubber latex composites by employing corn derivative bio‐fillers

Abstract: This study aims to investigate the viability of employing corn‐based fillers (powdered corn grain [CG], corn flour [CF] and cornstarch [CS]) to improve the biodegradability of natural rubber latex (NRL) composites by varying filler loading from 0 to 50 phr. Notable variation in both physical and mechanical properties were observed for the different filler types, with CG‐filled NRL demonstrating the better adhesion with NRL. Thus, CG‐filled composites were selected for investigation of biodegradability. Increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…The maximum values of elongation at break of NR–B at 392.0% and NR–W at 302.7% were obtained at filler loading of 20 phr and 60 phr, which were 3.5-fold and 2.7-fold increases of that of the NR film, respectively. However, the values relatively decreased with further increases in filler loading beyond the optimal point, because the elasticity of the rubber chains was reduced when filler particles exceeded a certain amount in the rubber matrix [ 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The maximum values of elongation at break of NR–B at 392.0% and NR–W at 302.7% were obtained at filler loading of 20 phr and 60 phr, which were 3.5-fold and 2.7-fold increases of that of the NR film, respectively. However, the values relatively decreased with further increases in filler loading beyond the optimal point, because the elasticity of the rubber chains was reduced when filler particles exceeded a certain amount in the rubber matrix [ 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…The previous studies demonstrated the limitations of polar filler loading in NR composites. They found the tensile strength of the NR composite increased with increasing the filler content up to a maximum value (20–60 phr) and then decreased [ 12 , 13 , 31 , 32 , 37 ]. Higher filler loading in NR composite could lead to formation of filler agglomeration and undispersed filler in NR matrix, resulting in a weak filler–rubber interaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CG loadings greater than 20 phr of tensile retention are reduced, implying the rapid loss of initial tensile strength under ageing circumstances at larger biofiller loadings. As a result, the most ideal CG loading in NR latex films was determined to be 20 phr for the manufacture of biodegradable NR gloves, in line with ASTM D3578, which reported a biodegradability of roughly 50% after 15 weeks of soil burial [ 64 ].…”
Section: Preparation and Characterization Of Latex-based Waste Natural Filler Compositementioning
confidence: 99%
“…In order to investigate in vitro drug release, The sustained release of curcumin from the ENR-graft-NVCL was obaserved at 20 °C and 40 °C . The release kinetics from the sample shows two stages: an initial fast release before the inflections (stage I) followed by a slow and constant release (stage II) [29][30]. In stage I, there were initial rapid release from the electrospun mats, then the release ceased and the remainder of the drug was released in stage II.…”
Section: Mechanical Properties and Morphologymentioning
confidence: 99%